2009
DOI: 10.1007/s12149-009-0304-y
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT image fusion error due to urinary bladder filling changes: consequence and correction

Abstract: Caution should be exerted during the interpretation of PET/CT scans of the pelvis as there is significant upward expansion of UB on PET compared with CT that appears to be exaggerated by OC use, likely due to additional fluid load. The PET/CT fusion errors of UB can be substantially resolved through a separate PLV acquisition presumably due to the shorter time interval of UB scan completion between CT and PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…After the segmentation, the bladder was analytically projected with the same projector that was used for the iterative reconstruction, generating new analytical sinograms of the bladder only. Segmenting directly from a fused CT image would avoid the step of the first reconstruction, but since the bladder volume will vary during the acquisition, and as PET and CT acquisitions are not simultaneous, there will be a size mismatching between CT and PET, making the PET segmentation more convenient for the particular case of the bladder (Heiba et al 2009). This limitation may be diminished if simultaneous PET-MR systems are utilised, where the bladder could be accurately segmented from the MR co-registered image.…”
Section: Discussionmentioning
confidence: 99%
“…After the segmentation, the bladder was analytically projected with the same projector that was used for the iterative reconstruction, generating new analytical sinograms of the bladder only. Segmenting directly from a fused CT image would avoid the step of the first reconstruction, but since the bladder volume will vary during the acquisition, and as PET and CT acquisitions are not simultaneous, there will be a size mismatching between CT and PET, making the PET segmentation more convenient for the particular case of the bladder (Heiba et al 2009). This limitation may be diminished if simultaneous PET-MR systems are utilised, where the bladder could be accurately segmented from the MR co-registered image.…”
Section: Discussionmentioning
confidence: 99%
“…Heiba et al (31), in reviewing integrated PET/CT images, observed considerable variation in the shape of the urinary bladder between the CT and PET scans and reported that this error can be significantly minimized by repeating the PET and CT scans of the pelvis in a single bed within a short period of one another. We did not observe any problem related to coregistration, even in a patient with a false-positive result (Fig.…”
mentioning
confidence: 99%
“…Fluids constantly move within the body. This manifests in a likely expansion of the bladder [ 13 ], but also in a change of stomach and intestine locations [ 14 ]. Thus, imaging the bladder, the stomach, the intestines and their surroundings can pose additional challenges [ 15 ].…”
Section: Introductionmentioning
confidence: 99%